Psycho-Social Consequences in Adolescents with Divorced Parents and Their Minimization - Tallushi, Esjurda; Biba, Gjylse; Isufi, Temisa (European Journal of Sustainable Development, 2017)
In modern times, where individualism and urbanization prevail, families experience great challenges not only in their structure, but also in their function. Family as the safest shelter for children/adolescents loses its sense when it is experienced the divorce of parents. The psycho-social consequences of some of them are evident in the creation of new social relationships, attitudes and behavior towards others and each parent, but also in their opinions, self-esteem, self-confidence, especially when considered problematic relationships such as parent-parent, adolescent-parent, that causes stress, psycho-emotional instability, up to anxiety, depression. The main purpose of this study is to identify the psychological and social consequences of children with divorced parents, which also determine the important role of each parent and supporting institutions such as school, society, professionals such as social workers/psychologists in treating and minimizing them. This paper is a qualitative research based on live interviews with two-line open-ended questions: subjects who directly experience divorce as adolescent boys and girls, aged 14-16 in high school. There were also interviews with divorced couples to understand how adolescents are experiencing the divorce, seen from their parents’ point of view. An important part is also the interviewing of subjects dealing with the treatment of minimizing its consequences, ie professionals working and staying close to these adolescents as teachers of a high school in Kavaja/Albania, social workers and psychologists of the school and the district court that is responsible for the assignment of parental custody, to understand the support that approaches adolescents. Selection of subjects was done through intentional sampling, were identified cases of families whith divorced couples with adolescent children and who have legally completed this process at the First Instance District Court of Kavaja/Albania. The results of this study serve to make people aware of the concrete psycho-social consequences of adolescents experiencing parent divorce and how can be improved their future treatment by their parents, professionals in order to mitigate the negative effects of divorce in the family. Keywords: divorce, adolescent, psycho-social consequences, treatment, parent, teacher, psychologist/social worker.